Proteomics of neural stem cells - Skalníková, Helena; Vodička, Petr; Gadher, Suresh Jivan; Kovářová, Hana (Expert review of proteomics, 2008)
The isolation of neural stem cells from fetal and adult mammalian CNS and the demonstration of functional neurogenesis in adult CNS have offered perspectives for treatment of many devastating hereditary and acquired neurological diseases. Due to this enormous potential, neural stem cells are a subject of extensive molecular profiling studies with a search for new markers and regulatory pathways governing their self-renewal as opposed to differentiation. Several in-depth proteomic studies have been conducted on primary or immortalized cultures of neural stem cells and neural progenitor cells, and yet more remains to be done. Additionally, neurons and glial cells have been obtained from embryonic stem cells and mesenchymal stem cells, and proteins associated with the differentiation process have been characterized to a certain degree with a view to further investigations. This review summarizes recent findings relevant to the proteomics of neural stem cells and discusses major proteins significantly regulated during neural stem cell differentiation with a view to their future use in cell-based regenerative and reparative therapy.
Keywords: kmenové buňky; Proteomics; Proteins; buněčná diferenciace; Stem Cells; lidé; Neurons; Cell Differentiation; Financing, Organized; proteiny; financování organizované; Humans; neurony; proteomika